Junkyard planet : travels in the billion-dollar trash trade - Minter, Adam, 1970- (Bloomsbury Press, 2013)
"When you drop your Diet Coke can or yesterday's newspaper in the recycling bin, where does it go? Probably halfway around the world, to people and places that clean up what you don't want and turn it into something you can't wait to buy. In Junkyard Planet, Adam Minter-- veteran journalist and son of an American junkyard owner-- travels deeply into a vast, often hidden, multibillion-dollar industry that's transforming our economy and environment. Minter takes us from back-alley Chinese computer recycling operations to recycling factories capable of processing a jumbo jet's worth of trash every day. Along the way, we meet an international cast of characters who have figured out how to squeeze Silicon Valley-scale fortunes from what we all throw away. Junkyard Planet reveals how "going green" usually means making money-- and why that's often the most sustainable choice, even when the recycling methods aren't pretty. With unmatched access to and insight on the waste industry, and the explanatory gifts and an eye for detail worthy of a John McPhee or William Langewiesche, Minter traces the export of America's garbage and the massive profits that China and other rising nations earn from it. What emerges is an engaging, colorful, and sometimes troubling tale of how the way we consume and discard stuff brings home the ascent of a developing world that recognizes value where Americans don't. Junkyard Planet reveals that Americans might need to learn a smarter way to take out the trash"--Dust jacket flap.